2018
DOI: 10.3390/su10020556
|View full text |Cite
|
Sign up to set email alerts
|

A Moderated Mediation Model for Board Diversity and Corporate Performance in ASEAN Countries

Abstract: Despite the major investigations in prior studies for direct links among board diversity and corporate performance, the literature has not covered many indirect associations among them. This article analyzes the association between board diversity (gender and foreigner) and corporate performance by focusing on the mediating role of corporate social responsibility reporting (CSRR) and the moderated mediation role of South East Asian (ASEAN) countries through new institutional theory, which consists of legitimac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 72 publications
(85 reference statements)
2
20
0
Order By: Relevance
“…His findings largely support the proposition that the link between gender diversity on boards and firms' financial performance is indirect and mediated by CSP, which serves as a means of responding to stakeholders' needs and interests. Moreover, E‐Vahdati et al (2018) studied the indirect relationship between board diversity, defined as gender diversity and foreign director representation, and the performance of firms from the Association of Southeast Asian Countries. They emphasise that the disclosure of information about CSR per the Global Reporting Initiative guidelines plays a mediating role in the relationship between the proportion of women on boards and the firms' financial performance.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…His findings largely support the proposition that the link between gender diversity on boards and firms' financial performance is indirect and mediated by CSP, which serves as a means of responding to stakeholders' needs and interests. Moreover, E‐Vahdati et al (2018) studied the indirect relationship between board diversity, defined as gender diversity and foreign director representation, and the performance of firms from the Association of Southeast Asian Countries. They emphasise that the disclosure of information about CSR per the Global Reporting Initiative guidelines plays a mediating role in the relationship between the proportion of women on boards and the firms' financial performance.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 99%
“…More specifically, Galbreath (2018) offers evidence of an indirect effect between board gender diversity and financial performance through the mediating role of CSR. Furthermore, E‐Vahdati et al (2018) have investigated the relationship between board diversity (gender and foreignness) and corporate performance by focusing on the mediating role of CSR reporting.…”
Section: Introductionmentioning
confidence: 99%
“…A study in emerging markets explains that gender diversity affects corporate performance directly and indirectly through social responsibility. These interactions could be additionally moderated by cultural effects (E-Vahdati et al , 2018). The interaction is further confirmed in developed economies, indicating that the effect was full and not partial (Galbreath, 2018).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Also, if a group is mainly composed of females, individuals in the group tend not to delay their loan payments [21]. Another line of studies has reported that the presence of females on the board positively affects a firm's corporate social responsibility (CSR) rating and performance [22,23].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%